Analysis Of The Case Of The Death Of 6 FPI Soldiers in Tthe Perspective Of Law And Human Rights - Zalwa Widyadhana zalwa; Najwa Lutfi; Reva Alya; Tita Amalia (International Journal of Law and Legal Ethics, 2025)
On December 7, 2020, six members of the Islamic Defenders Front (FPI) were shot near Kilometer 50 of the Jakarta–Cikampek Toll Road, raising serious questions regarding Indonesian law enforcement and human rights protection. This research looks at the police's criminal culpability, how human rights standards were used during the inquiry, and how the case affected public confidence. This study examines legal documents such the 1945 Constitution, the Criminal Code, Law No. 39 of 1999 on Human Rights, and the investigative report by Komnas HAM using a normative juridical approach. The results demonstrate that despite the police's claim of self-defense, two inmates' deaths suggested possible human rights breaches. The officers' acquittal by the court exposed flaws in openness and accountability. This case reflects the urgent need for reform in law enforcement and stronger protection of human rights in Indonesia.